Extended gate field-effect-transistor for sensing cortisol stress hormone - Shokoofeh Sheibani (Nature Portfolio, 2021)
Wearable, real-time devices that can monitor hormones are important for personalized healthcare. Here, a platinum/graphene aptamer extended gate field effect transistor is shown to detect cortisol, the primary stress hormone, in physiological fluid.